The Effect of Cigarette Smoking during Pregnancy on Endocrine Pancreatic Function and Fetal Growth: A Pilot Study - Lockhart, Fatima; Liu, Anthony; Champion, Bernard Linton; Peek, Michael John; Nanan, Ralph Kay Heinrich; Poulton, Alison Sally (Frontiers in Public Health, 2017)
Introduction Cigarette smoking in pregnancy is a common cause of fetal growth restriction. We aimed to investigate endocrine pancreatic function of mother–infant dyads in relation to cigarette smoking, as a possible mechanism for the poor fetal growth. Methods Prospective study of smoking mothers (10 cigarettes or more per day, self-reported to the midwife) and non-smoker control mothers during their first pregnancy. Insulin, glucose, C-peptide, HbA1C, fructosamine, prolactin, serotonin, and cortisol were measured in maternal blood at 24–26 weeks and in umbilical cord blood at birth. Cotinine was also measured in cord blood. Results Of 37 smokers and 36 non-smokers recruited, cord blood was obtainable from 38 babies (19 in each group). In utero cigarette exposure was associated with lower birthweight (3,035 ± 490 versus 3,405 ± 598 g, p = 0.005), with linear modeling of the smoking cohort showing a 41 g reduction for every increase of one cigarette smoked per day (95% CI −71 to −11 g, p = 0.010). There were no differences between groups in indices of maternal or perinatal endocrine pancreatic dysfunction. Heavier smoking independently correlated with higher maternal fasting levels of glucose (p = 0.044) and C-peptide (p = 0.011). We did not observe any significant associations between the daily number of cigarettes and any of the cord blood parameters. We also looked for differences between cohorts based on infant gender. Serotonin levels were higher in smoking mothers with male fetuses (p = 0.01 to p = 0.004). Conclusion Endocrine pancreatic dysfunction does not appear to be a major contributing factor to nicotine-associated fetal growth restriction. The higher serotonin levels in smoking mothers carrying male infants is of uncertain significance but could be a manifestation of gender differences in susceptibility to the long-term effects of cigarette smoking.